2020
DOI: 10.1038/s41431-020-0652-6
|View full text |Cite
|
Sign up to set email alerts
|

AAV-mediated FOXG1 gene editing in human Rett primary cells

Abstract: Variations in the Forkhead Box G1 ( FOXG1) gene cause FOXG1 syndrome spectrum, including the congenital variant of Rett syndrome, characterized by early onset of regression, Rett-like and jerky movements, and cortical visual impairment. Due to the largely unknown pathophysiological mechanisms downstream the impairment of this transcriptional regulator, a specific treatment is not yet available. Since both haploinsufficiency and hyper-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
20
1
Order By: Relevance
“…Two major concerns regarding this potential therapeutic approach still persist, particularly viral toxicity and heterogenous distribution of MeCP2 gene expression throughout the brain, since local overexpression causes severe symptoms, as observed in MeCP2 duplication syndrome [ 111 ]. Recently, another publication showed that AAV9 coupled with the use of CRISPR/Cas9 was able to target and correct FOXG1 in both RTT hiPSCs and hiPSC-derived neurons, with an efficiency of 20–35% [ 112 ]. Very close to clinical trials is also an AAV-mediated MeCP2 gene expression cassette [ 113 ] with endogenous regulatory elements, already tested in pre-clinical mouse models [ 114 ].…”
Section: Future Clinical Translation Of Hpsc Technology In Rttmentioning
confidence: 99%
“…Two major concerns regarding this potential therapeutic approach still persist, particularly viral toxicity and heterogenous distribution of MeCP2 gene expression throughout the brain, since local overexpression causes severe symptoms, as observed in MeCP2 duplication syndrome [ 111 ]. Recently, another publication showed that AAV9 coupled with the use of CRISPR/Cas9 was able to target and correct FOXG1 in both RTT hiPSCs and hiPSC-derived neurons, with an efficiency of 20–35% [ 112 ]. Very close to clinical trials is also an AAV-mediated MeCP2 gene expression cassette [ 113 ] with endogenous regulatory elements, already tested in pre-clinical mouse models [ 114 ].…”
Section: Future Clinical Translation Of Hpsc Technology In Rttmentioning
confidence: 99%
“…After incubating for 4 h at 37 °C with 5% carbon dioxide, the medium was replaced with NEUROBASALTM medium supplemented with 2% B27. The neurons were used for experiments after 7‐d culture ( Croci et al, 2020 ; Yan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Using MECP2-knockout mice, encouraging pre-clinical results with increased survival and body weight have been seen after intracisternal delivery of AAV vectors encoding MECP2 (Gadalla et al, 2017;Sinnett et al, 2017;Sandweiss et al, 2020). An alternative approach is the use of CRISPR/Cas9 genome editing that has been shown to be efficient at correcting FOXG1 variants in human RTT patient-derived fibroblasts and induced pluripotent stem-derived neurons using AAV9 vectors (Croci et al, 2020). Human clinical trials remain to be initiated.…”
Section: Neurodevelopmental Disorders Rett Syndrome (Rtt)mentioning
confidence: 99%